Phase and group velocities of ectromagnetic eigen waves of left-hand material slab - Azarenkov, N.A.; Galaydych, V.K.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2012)
This work is devoted to the study of phase and group velocities of the surface eigen electromagnetic waves that propagate along the left-handed planar slab that bounded by the dielectrics with different permittivity values at the both sides of considered slab. It has been shown that the change of metamaterial slab thickness substantially influences on dispersion of the waves under investigation. Работа посвящена изучению фазовой и групповой скоростей собственных поверхностных электромагнитных волн, распространяющихся вдоль плоского слоя левостороннего материала, ограниченного диэлектриками с различными значениями диэлектрической проницаемости. Показано, что изменение толщины слоя метаматериала существенно влияет на фазовую и групповую скорости исследуемых волн. Роботу присвячено вивченню фазової і групової швидкостей власних поверхневих електромагнітних хвиль, що поширюються уздовж плоского шару лівостороннього матеріалу, що обмежений діелектриками з різними значеннями діелектричної проникності. Показано, що зміна товщини шару метаматеріалу суттєво впливає на фазову і групову швидкості хвиль, що вивчаються.